2020
DOI: 10.3390/ijerph17020551
|View full text |Cite
|
Sign up to set email alerts
|

Great Expectations: A Qualitative Analysis of the Factors That Influence Affective Forecasts for Exercise

Abstract: The extent to which people expect to feel pleasure during exercise is proposed to influence an individual’s decision to be active. In order to identify the factors that shape this affective forecast for exercise, this study explored what people think about when creating their affective forecast for exercise. Thirty-one inactive participants provided an affective forecast for a moderate intensity exercise session using the global affective forecast questionnaire. Immediately after, they were asked a series of q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 52 publications
1
21
0
1
Order By: Relevance
“…Previous studies have suggested that a hedonic approach to exercise may be a promoter of enjoyment ( Ekkekakis and Zenko, 2016 ; Murphy and Eaves, 2016 ; Calder et al, 2020 ), and that the preference/tolerance intensity-traits may be related to this state ( Ekkekakis et al, 2008 ; Box and Petruzzello, 2020 ). The present results seem to support the concept that intensity-traits are to some extent associated with enjoyment (small-to-moderate effect).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have suggested that a hedonic approach to exercise may be a promoter of enjoyment ( Ekkekakis and Zenko, 2016 ; Murphy and Eaves, 2016 ; Calder et al, 2020 ), and that the preference/tolerance intensity-traits may be related to this state ( Ekkekakis et al, 2008 ; Box and Petruzzello, 2020 ). The present results seem to support the concept that intensity-traits are to some extent associated with enjoyment (small-to-moderate effect).…”
Section: Discussionmentioning
confidence: 99%
“…In these multifactorial exercising interactions, promoting the dynamics that aim at enhancing the quality of the individual’s subjective experience can be challenging. For that matter, enjoyment was highlighted as a significant determinant of intention to continue and exercise adherence ( Nielsen et al, 2014 ; Calder et al, 2020 ; Chen et al, 2020 ). However, due to the intrinsic characteristics of the activities offered in health clubs, promoting exercisers enjoyment may not be easy.…”
Section: Introductionmentioning
confidence: 99%
“…Regular exercise participation in the geriatric population is linked to their outcome expectations. [1][2][3][4][5] Outcome expectation for exercise is defined as the perceived effects of participating in exercise or physical activity. 6 It encompasses three related but conceptually independent sub-domains: physical, social, and self-evaluative outcome expectations.…”
Section: Introductionmentioning
confidence: 99%
“…[7][8] It has been shown to predict physical activity in older adults, with positive outcome expectations linked to a greater likelihood of exercising. 1,[7][8] The exercise outcomes expectations of older adults include: 1) prevention of disease and health complications, and 2) promotion of social engagement and psychological needs. [1][2][3][4][5] Exercise participation has been shown to reduce the risk of cardiovascular disease in older adults while improving physical functioning and quality of life.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation